Engineering for Cosmetic Product Quality and Supply Continuity: Modeling Defect Escape, Batch Release Latency, and Complaint Risk Under Measurement Uncertainty - Sreymao Pech Sreymao Pech; Ayesha Rahman Ayesha Rahman (Kalam Practica Media, 2025)
This article presents an engineering-oriented framework that treats cosmetic quality assurance as an end-to-end decision system and quantifies how uncertainty propagates from incoming raw material variability through in-process controls, laboratory testing, and release decisions into distributional outcomes relevant to production and brand risk, including probability of defect escape, probability of false rejection, time-to-release distributions, complaint incidence risk, and expected cost per batch. A scenario-based quantitative study is developed for representative skin-care and color cosmetic products across three risk profiles, comparing four operational architectures: baseline end-of-line testing, increased testing density without governance, model-based risk scoring with limited drift handling, and a governance-optimized two-tier approach that constrains nuisance rejections while improving early detection through drift-aware controls, stratified sampling, and staged release decisions. Results indicate that defect escape is dominated by sampling and release latency tails rather than by mean lab accuracy, that expanding tests without governance can increase false rejection and slow release, and that a two-tier governed strategy reduces defect escape while stabilizing throughput and complaint risk. Up to three copy-ready tables and full prompts for data-driven figures are provided for Techne submission.